EVALUASI EFEKTIVITAS PROSES PRODUKSI KARET REMAH DAN RIBBED SMOKED SHEET BERDASARKAN NILAI OVERALL EQUIPMENT EFFECTIVENESS (OEE) - Tanto Pratondo Utomo; Erdi Suroso; Harun Al Rasyid; Muhamad Pandutyas; Adven Bangun Sihite (JURNAL AGROTEKNOLOGI, 2016)
Performance and productivity of natural rubber agroindustry could be determined by its overall equipment effectiveness (OEE) value because OEE is the best way to monitor the production efficiency which consisted of availability ratio (AR), performance efficiency (PE), and quality rate (QR). . By using the OEE, the Standard Indonesia Rubber (SIR) and Ribbed Smoked Sheet (RSS) Factory find the sources of its productivity loss. The aim of this research were to determine the OEE of RSS Rubber Factory and its source of productivity loss. This research was conducted in one SIR 3 and one RSS Factory in Lampung Province. The research was conducted by field survey. The primary and secondary data collected was analyzed descriptively and were presented in tables and diagrams. The result showed that the average OEE of SIR Factory was 71.68 percent which was consisted of 89.58 percent of AR, 80.29 percent of PE, and 99.81 percent of QR; meanwhile OEE RSS Factory was of 46.47 percent that consisted of 95.92 percent of availability ratio, 48.42 percent of performance effciency, and 99.97 percent of quality product . The performance efficiency was the lowest among three components of RSS Rubber Factory OEE. This low value of performance efficiency showed that the speed of the production process is far from predetermined or designed production speed rate. Keywords: OEE, rubber factory, SIR 3, RSS